Out-of-body experiences associated with seizures - Greyson, Bruce; Fountain, Nathan B.; Derr, Lori L.; Broshek, Donna K. (Frontiers in Human Neuroscience, 2014)
Alterations of consciousness are critical factors in the diagnosis of epileptic seizures. With these alterations in consciousness, some persons report sensations of separating from the physical body, experiences that may in rare cases resemble spontaneous out-of-body experiences. This study was designed to identify and characterize these out-of-body-like subjective experiences associated with seizure activity. 55% of the patients in this study recalled some subjective experience in association with their seizures. Among our sample of 100 patients, 7 reported out-of-body experiences associated with their seizures. We found no differentiating traits that were associated with patients’ reports of out-of-body experiences, in terms of either demographics; medical history, including age of onset and duration of seizure disorder, and seizure frequency; seizure characteristics, including localization, lateralization, etiology, and type of seizure, and epilepsy syndrome; or ability to recall any subjective experiences associated with their seizures. Reporting out-of-body experiences in association with seizures did not affect epilepsy-related quality of life. It should be noted that even in those patients who report out-of-body experiences, such sensations are extremely rare events that do not occur routinely with their seizures. Most patients who reported out-of-body experiences described one or two experiences that occurred an indeterminate number of years ago, which precludes the possibility of associating the experience with the particular characteristics of that one seizure or with medications taken or other conditions at the time.